MEMBACA RESISTENSI TERHADAP KOLONIALISME DALAM CERPEN â€œSAMIN KEMBARâ€ KARYA TRIYANTO TRIWIKROMO - Efendi, Agik Nur (Universitas Pendidikan Indonesia, 2016)
AbstractÂ This article aims to describe the form of post-colonial resistance from the standpoint of mimicry, hybridity, ambivalence, diaspora, identity is represented on the short story works Triyanto Triwikromo Samin Twins. Samin cePen Twins lift setting colonialism in the area of Sawahlunto, Blora, Grobogan, and Bojonegoro in 1897an. This short story tells the story of Resident Assistant Blora who tried to interrogate the leader who claimed to be Samin. Instead of trying to interrogate, Assistant Resident've got a resistance of interlocutor. Assistant Resident menamkan colonial process in Blora and surrounding communities. The story contains the story of the history of the Dutch colonial times so that the right to be assessed by post-colonial theory. Operationalization of post-colonial theory in the study of literary texts illustrated by efforts to study literary text data that relates to consciousness colonized on the colonizers. Step study conducted dengana, determination of data sources, collection and classification of data, and data analysis. Postcolonial analysis is expected to help in the discovery of awareness of nationalism in order to sustain the unity of the nation.Keywords: post-colonial, resistance, short stories, Samin, Assistant Resident